Sociology of Education – Theories, Communities, Contexts - Vincze, Zsófia (Central European Journal of Educational Research, 2023)
Bibliography of the reviewed book: Pusztai, G. (Eds.), (2023). Sociology of Education – Theories, communities,contexts. Debrecen University Press.